Use of Mineral Fertilizers in Vineyards Effects on Productivity - Tashiboev Shuxratbek Tursunboevich; Najmudinova Dilfuzaxon Sharobidinovna; Berdaliev Husniddin Norqul oglu (Genius Journals, 2022)
The article provides information on the effect of methods and timing of application of organic and mineral fertilizers on raisins in irrigated gray soils and light meadow soils Kishmish Sogdiyona and Kishmish Vira
Keywords: Grape Varieties; Kishmish Sogdiyona; Kishmish Vira; Yield